Association between alcohol intoxication and mortality in severe traumatic brain injury in the emergency department: a retrospective cohort. (22nd October 2020) - van Wijck, Suzanne F.; Kongkaewpaisan, Napaporn; Han, Kelsey; Kokoroskos, Nikolaos; Kongwibulwut, Manasnun; King, David R.; van der Wilden, Gwendolyn M.; Krijnen, Pieta; Schipper, Inger B.; Velmahos, George C.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Acute alcohol intoxication is very common in patients with severe traumatic brain injury (TBI). Whether there is an independent association between alcohol intoxication and mortality is debated. This study hypothesized that alcohol intoxication is independently associated with less mortality after severe TBI (sTBI). Methods: This retrospective observational cohort study included all patients with sTBI [head-Abbreviated Injury Score (AIS) ≥3, corresponding to serious head injury or worse] admitted from 1 January 2011 to 31 December 2016 in an academic level I trauma center. Patients were classified as with alcohol intoxication or without intoxication based on blood alcohol concentration or description of alcohol intoxication on admission. The primary endpoint was in-hospital mortality. Multivariable logistic regression analysis, including patient and injury characteristics, was used to assess independent association with alcohol intoxication. Results: Of the 2865 TBI patients, 715 (25%) suffered from alcohol intoxication. They were younger (mean age 46 vs. 68 years), more often male (80 vs. 57%) and had a lower median Glasgow Coma Scale upon arrival (14 vs. 15) compared to the no-intoxication group. There was no difference in injury severity by head AIS or Rotterdam CT. Alcohol intoxication had an unadjusted association with in-hospital mortality [unadjusted odds ratio (OR) 0.51; 95% confidence interval (CI), 0.38–0.68]; however, there was no independent association after adjusting for potentially confounding patient and injury characteristics (adjusted OR 0.72; 95% CI, 0.48–1.09). Conclusion: In this retrospective study, there was no independent association between alcohol intoxication and higher in-hospital mortality in emergency patients with sTBI.